(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Spontaneous bile duct perforation causing biliary peritonitis in children is an exceedingly rare occurrence. This condition poses an uncommon and potentially hazardous reason for acute abdominal symptoms. A pre-surgical diagnosis remains a rarity. We present a case of a five-month-old infant displaying gradual fever, jaundice, pale-colored stool, and abdominal distension for 12 days who was referred to NINMAS for a 99mTc-HIDA scan to investigate extrahepatic biliary atresia. The scan unveiled substantial radionuclide activity around the abdominal boundary in 2-hour, 4-hour, and 24-hour views, suggesting abnormal radioactivity in ascitic fluid due to bile leakage. Ultrasonography at NINMAS revealed a contracted gallbladder and moderate ascites. This study reviews and discusses the pathogenesis of this condition. Bangladesh J. Nuclear Med. 26(2): 215-217, 2023